Jaran Kepang Art as a Means of Character Education in Paguyuban Rukun Tri Santoso - Rebeka Sri Minati; Dionisius Heckie Puspoko Jati; Nani Mediatati (Jayapangus Press, 2026)
Jaran Kepang is widely recognized as a form of traditional cultural heritage and community entertainment; however, its function as a medium for character education within art communities has not been sufficiently explored. In fact, traditional performance practices contain educational values that contribute to the formation of individual and social character, particularly among young community members. This study aims to examine the presentation of Rukun Tri Santoso and to identify the character education values embedded in its performance and community activities. A qualitative descriptive approach was employed. Data were collected through participatory observation of performances, in-depth interviews with the community leader, the handler, six dancers, four gamelan musicians, and three supporting members, as well as documentation analysis. Data validity was ensured through source triangulation and member checking. The findings indicate that the Jaran Kepang performance integrates dance movements, gamelan accompaniment, costumes, properties, and performance procedures that are rich in symbolic meanings. These elements reflect character values such as discipline, responsibility, teamwork, mutual cooperation (gotong royong), religiosity, respect, and appreciation of local culture. Importantly, these values are not only manifested during public performances but are consistently internalized throughout rehearsal processes, role distribution, and daily social interactions among paguyuban members. In conclusion, Jaran Kepang functions as an informal, community-based character education agent through embodied cultural practices. This study demonstrates has strong potential as a local wisdom based medium for character education that can be applied in both formal and non-formal educational contexts, particularly in supporting cultural preservation and youth character development.